1999
DOI: 10.1136/hrt.81.6.618
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and respiratory muscle strength in chronic heart failure: comparison between ischaemic and idiopathic dilated cardiomyopathy

Abstract: Objective-To compare pulmonary function and respiratory muscle strength in patients with ischaemic and idiopathic dilated cardiomyopathy, well matched for indices of heart failure. Methods-The study involved 30 patients with ischaemic cardiomyopathy and 30 with idiopathic dilated cardiomyopathy. The groups were well matched for age, weight, and clinical severity of cardiac dysfunction as assessed by ejection fraction and the New York Heart Association functional class. There were more smokers in the ischaemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 15 publications
1
31
1
7
Order By: Relevance
“…The mechanism for the loss of TLC in CHF remains controversial with factors such as changes in lung fluid balance, cardiomegaly, increased central blood volume, respiratory muscle weakness and airway remodeling being cited as potential causes. [20][21][22][23] However unlike Nannas et al 3 , we did not find that IC was an independent predictor of VO 2peak in CHF. After accounting for the variance due to LLCT, we found that adding IC did not significantly improve the model for determining VO 2peak .…”
Section: Discussioncontrasting
confidence: 92%
“…The mechanism for the loss of TLC in CHF remains controversial with factors such as changes in lung fluid balance, cardiomegaly, increased central blood volume, respiratory muscle weakness and airway remodeling being cited as potential causes. [20][21][22][23] However unlike Nannas et al 3 , we did not find that IC was an independent predictor of VO 2peak in CHF. After accounting for the variance due to LLCT, we found that adding IC did not significantly improve the model for determining VO 2peak .…”
Section: Discussioncontrasting
confidence: 92%
“…Some of these data also suggest that the degree of impairment in respiratory muscle function parallels the severity of the cardiac dysfunction, its aetiology [115,[118][119][120][121], clinical prognosis [122] and, interestingly, increased peripheral chemosensitivity [123], a finding possibly related to an increase in sympathetic activation [124]. Importantly, some investigators have also reported on the relationship between the severity of respiratory muscle dysfunction and baseline dyspnoea [117], exertional dyspnoea [125], peak V′O 2 [119] and the abnormal V′E/V′CO 2 slope [121] in patients with heart failure.…”
Section: Alveolar-capillary Membrane Dysfunctionmentioning
confidence: 97%
“…Results from volitional as well as non-volitional tests using phrenic nerve stimulation have confirmed the decrease in inspiratory (mouth or transdiaphragmatic) pressure in CHF [3133]. The inability to generate normal inspiratory pressure is independent of the etiology of disease [34,31,10,35]. Notably, the prevalence of this inspiratory dysfunction in CHF, defined arbitrarily as MIP < 70% predicted [35,36], does appear to depend on age.…”
Section: Evidence Of Inspiratory Dysfunction – Heart Failure and Amentioning
confidence: 97%